"To Reverse or Not To Reverse?": The Answer Is Clear!. Issue 1 (February 2017) - Murphy, G. S.; Kopman, A. F.
Abstract : (Abstracted from Anesthesiology, 125:611–614, 2016) Residual neuromuscular blocks after operations have increased morbidity and mortality in surgical patients. Postoperative residual neuromuscular block (PRNB) has been linked to respiratory issues and postoperative pneumonia (POP), both in the immediate and long term.